El realismo moral de Markus Gabriel contra el Antropoceno - Villapudua, Karla (2024)
The objective of this article is to dialogue with the new moral realism of Markus Gabriel to affirm the reality of the Anthropocene in the face of postmodern denialism. In order to do this, we review some characteristics of the so-called postmodernity, and its manifestations in politics, ethics and epistemology. Next, we analyze Markus Gabriel's new moral realism due to the fact that only from a realistic and universalist ethical position will it be possible to counteract the climate catastrophe. As a result of the above, we reflect on the horizons that can enable moral realism in various areas of life. as a viable alternative to clarify why we cannot continue perpetuating the relativism of climate events, and also enable the intensification of policies focused on carrying out actions that combat the destruction of life on the planet.